Dynamic effects of an anticipated switch from destination- to origin-based commodity taxation - Andreas Haufler; Søren Bo Nielsen (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
This paper investigates the macroeconomic and welfare effects of an anticipated future switch from destination- to origin-based commodity taxation. We set up an intertemporal representative agent model of an open economy and study especially consumption, investment and trade balance responses to the commodity tax reform. The anticipation effects on the macroeconomy are significant, whereas their welfare implications are not.
Keywords: 330